Expression and clinical significance of LncRNA Kcnq1ot1 in type 2 diabetes mellitus patients with osteoarthritis - Hai Hu; Can Zhou; Binbin Jiang; Song Wu; Ting Cai; Jie Yu; Liguo Zhu; Biao Zhou (BMC Endocrine Disorders)
Abstract Objective We aimed to investigate the expression of lncRNA Kcnq1ot1 in T2DM patients with OA, as well as its correlation with serum inflammatory factors and clinical outcomes of the patients. Methods This prospective observational cohort study included a total of 50 patients with type 2 diabetes mellitus (T2DM), 50 patients with osteoarthritis (OA), and 51 patients with both T2DM and OA between March 2020 and March 2023. The serum TNF-α, interleukin (IL)-6, IL-1β and C-reactive protein (CRP) levels were measured using enzyme-linked immunosorbent assay (ELISA). To determine the expression of LncRNA Kcnq1ot1, RT-qPCR was used. Demographic, clinical statistics, lipid metabolism and nutritional indicators were collected. All data used SPSS 26.0 to statistical analyses. Results The T2DM + OA group had significantly higher BMI and LDLC levels compared to the T2DM group (p < 0.05). The serum levels of LncRNA Kcnq1ot1 were significantly higher in the T2DM + OA group compared to the OA group and T2DM group (p < 0.05). Pearson’s analysis supported a positive correlation between LncRNA Kcnq1ot1 and IL-6 and IL-1β levels. In addition, LncRNA Kcnq1ot1 could be a potential biomarker for diagnosing the occurrence of T2DM patients with OA. Moreover, LncRNA Kcnq1ot1, BMI, IL-6, Low density lipoprotein cholesterol (LDLC) were the risk factors for T2DM patients with OA. Conclusion This study showed that the serum LncRNA Kcnq1ot1 levels was remarkably elevated in T2DM patients with OA. This study might provide new targets and a comprehensive approach to treatment in T2DM patients with OA.